A Practical View of the State-of-the-Art of Lattice-Based Cryptanalysis - Mariano, Artur (2017)
This paper describes the lattice problems that are key in the study of lattice-based cryptography, identi es and categorizes methods for solving these problems, analyzes existing implementations of these algorithms, and extrapolates on the future of lattice-based cryptanalysis, based on the foreseeable advances in computer architecture. Some future lines ofwork are given, considering the existence of parallel architectures that seem adequate for current attacks.